Risk-based pricing of financial products - Mukatuni, Awelani Lynn (My University, 2022)
This is an analytical research that aims to contribute to the discussions around risk-based pricing of financial products. It aims at contributing a better understanding of the risk-based pricing model, its pros and cons, and areas of improvement in the consumer credit environment. The study uses real-life data and the risk-based pricing model to analyse suitable credit prices that would allow more people to afford taking up credit. The study uses the relationship between price sensitivity and the offered interest rate to support offered credit prices. The study also aims to analyse the national credit act regulations on the maximum interest rate that an institution can offer. The study includes sample calculations that were drawn from Standard and Captec banks under the assumption that the two banks are using the risk-based pricing model. The results revealed that the model allows for more borrowers to have access to credit by allowing lenders to charge a high interest rate to high-risk borrowers. The model rewards low risk borrowers and compensates lenders for extending credit to high-risk borrowers. An analysis of the National Credit Act (NCA) revealed that it allows for banks and borrowers to maximise profit and marginalise a great number of borrowers at the same time. Due to its simplicity, the NCA becomes a good model to use as a basis for offering interest rates for high-risk borrowers, thus increasing the number of borrower classes.
The thesis is submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the Master of Management in Finance and Investment
Keywords: Pre-distribution and Ownership; Financial product; Risk-Based Pricing; Financial risks; Credit; Credit price; Price sensitivity; SDG-8: Decent work and economic growth